Mixed Marriages in Indonesia and Citizenship Issues: a Call for Dual Citizenship Reform For Children From Mixed Marriages - Soesetyo, Setiawati (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
Law No. 1 of 1974 on Marriage Article 57 defines mixed marriages as marriage between two persons who in Indonesia are subject to different laws, due to differences in citizenship and one of the parties is a foreign national and one of the parties is an Indonesian national. While mixed marriages have occurred widely in Indonesia involving two people of different origins, religious beliefs, or ethics, the issue of citizenship arises when married couples involve two people of different nationalities. Some countries in the world allow instant citizenship by marriage. The State Republic of Indonesia acknowledges single citizenship under Law No. 12 of 2006 concerning Citizenship. The main idea of this journal is to highlight the issues of citizenship of offspring from mixed marriages. While children of mixed marriages may have dual citizenship until the age of 18, what are the implications for their citizenship in the future? In the context of the state, how does the government see this as the nation’s future generation?